2019
DOI: 10.3390/nano9030401
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of the Load of Transition Metal Oxides (Fe2O3, Co3O4, NiO and/or PdO) onto CeO2 Nanoparticles in Catalytic Steam Decomposition of n-C7 Asphaltenes at Low Temperatures

Abstract: The main objective of this work is the catalyst optimization of Fe2O3-, Co3O4-, NiO- and/or PdO- (transition element oxides—TEO) functionalized CeO2 nanoparticles to maximize the conversion of asphaltenes under isothermal conditions at low temperatures (<250 °C) during steam injection processes. Adsorption isotherms and the subsequent steam decomposition process of asphaltenes for evaluating the catalysis were performed through batch adsorption experiments and thermogravimetric analyses coupled to Fourier-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
72
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(80 citation statements)
references
References 61 publications
(86 reference statements)
7
72
0
Order By: Relevance
“…As can be seen, under the three atmospheres, the cracking of the asphaltenes occurs at several stages, and they start at 400, 426, and 465 °C for inert, air, and steam atmospheres, respectively [44,82,87]. Several authors explain this phenomenon due to the presence of a distribution of sizes of asphaltenes of high to low molecular weight, where the heavier fractions decompose at higher temperatures [30,45,88] and the different intensities of the different peaks is attributed to possible addition or aggregation reactions of n-C7 asphaltene after its initial cracking. After the asphaltene [49], inert gases [44], and air [82] performed at atmospheric pressure.…”
Section: Physical-chemical Properties Of Heavy (Ho) Extra-heavy Crudmentioning
confidence: 99%
See 4 more Smart Citations
“…As can be seen, under the three atmospheres, the cracking of the asphaltenes occurs at several stages, and they start at 400, 426, and 465 °C for inert, air, and steam atmospheres, respectively [44,82,87]. Several authors explain this phenomenon due to the presence of a distribution of sizes of asphaltenes of high to low molecular weight, where the heavier fractions decompose at higher temperatures [30,45,88] and the different intensities of the different peaks is attributed to possible addition or aggregation reactions of n-C7 asphaltene after its initial cracking. After the asphaltene [49], inert gases [44], and air [82] performed at atmospheric pressure.…”
Section: Physical-chemical Properties Of Heavy (Ho) Extra-heavy Crudmentioning
confidence: 99%
“…Additionally, the gasification of resins II and complex systems R:A (Resins: Asphaltenes) under isothermal and nonisothermal conditions, at temperatures below 240 • C. The authors found that the increase in content of resins II in the systems decreases the activation energy to carry out the decomposition of the system. Finally, considering the above, it is important to decompose these molecules in order to bring the crude oil to better viscosity conditions and API gravity to facilitate production, refinery, and transport operations [88]. However, the conventional thermal enhanced oil recovery processes do not generate an upgrading in the crude oil quality, due to the low temperatures at which it operates, since asphaltene and resins decompose mainly at temperatures above 400 • C [88].…”
Section: Interaction Between Heavy Crude Oil Fractions and Nanoparticlesmentioning
confidence: 99%
See 3 more Smart Citations